THE CONCEPT OF FUNCTION AND CONTEXT WITHIN THE FRAMEWORK OF THE COMMUNICATIVE APPROACH - Saidova Mamura Suleymanovna (Western European Studies, 2023)
The article examines the concepts of function and context in the context of a communicative approach to language. The communicative approach emphasizes language as a means of communication, where function and context play key roles. The functions of language can change at different levels, from the micro level within a sentence to the macro level in texts and discourses. Cultural context has a strong influence on the functions of language, and the metaphorical function and dynamic nature of the context add complexity to their understanding. The article also emphasizes the importance of teaching communicative competence, which requires the ability to adapt language to different situations and communication purposes.
Keywords: Communicative approach; language; language function